Cyperaceae endémicas del Perú - León, Blanca (2006)
The Cyperaceae are represented in Peru by 28 genera and 230 species (Brako & Zarucchi, 1993; Ulloa Ulloa et al., 2004), all herbaceous plants. Here we recognize seven endemic taxa in six genera. We assigned IUCN threat categories to five species. The endemic taxa are found in several kinds of environments of the Dry and Humid Puna, Mesoandean, and Humid Montane Forest regions, between 1350 and 4200 m elevation. Two endemic species have been reported to occur in protected areas.